An Intact Dopamine Sensitivity in the Brain: A Necessity to Recover Hyperprolactinemia and Galactorrhea in a Female Hemodialysis Patient? - Eva Philipse; Ester Philipse; Theodorus Twickler; Amaryllis Van Craenenbroeck; Marie Madeleine Couttenye; Luc Van Gaal (Case Reports in Nephrology)
A female hemodialysis patient with galactorrhea due to hyperprolactinemia was treated with different dialysis modalities to assess the effect on prolactin levels. A single session of both high-flux hemodialysis and hemodiafiltration resulted in decreased prolactin levels (16,6% and 77,2%, resp.). However, baseline prolactin levels measured immediately before the next dialysis session did not change markedly. After cabergoline treatment was started, prolactin levels normalized and galactorrhea disappeared. Thus, dopaminergic inhibition of prolactin secretion might be reduced in patients with end-stage renal disease. This dopaminergic resistance could be an important mechanism of hyperprolactinemia in hemodialysis patients and its subsequent treatment strategies.